M-mode echogram as a means of distinguishing between mild and severe mitral stenosis. Issue 5 (November 1981) - Hall, R; Austin, A; Hunter, S
Abstract : Fifty-two patients with pure mitral stenosis (27 with severe stenosis and 25 with mild stenosis) were studied to assess the ability of different M-mode echocardiographic measurements to separate mild and severe disease. Variables related to valve motion, for example diastolic closure rate, the mitral valve closure index, and the amplitude of valve motion, accurately divided patients with mitral stenosis from normal subjects but did not distinguish usefully between mild and severe disease. In contrast, variables dependent on left ventricular dimension change in diastole, for example the rapid filling period and the peak rate of left ventricular diastolic dimension change, accurately separated mild and severe disease. No patient with severe mitral stenosis had a rapid filling period, whereas 21 of the 25 patients with mild disease did have one. The peak rate of left ventricular diastolic dimension change was less than 10 cm/s or less than 2.4 cm/s per cm when normalised for left ventricular dimension in all patients with severe disease and in only six of the 25 patients with mild disease.